Ship structure reliability evaluation in design, maintenance phases - Ahmad Izadi (LAP Lambert Academic Publishing, 2019)
In the present study, the reliability evaluation application in design, maintenance and repair have been investigated for the ship hull girder. The objective of the project is to develop reliability based methods which are to be used for the design of ship structures, in particular by calibration of the safety factors in design rules. In order to evaluate the structure strength, the extended model of the ultimate limit state of hull-girder regarding corrosion and fatigue defect have been used based on probabilistic analysis that depends on time. The time-dependent reliability has been evaluated using minimum elastic section modulus required; this process in the case of fatigue in ship deck has been done using mechanical fracture and S-N curve. The results from the reliability evaluation using Monte-Carlo simulation method and First-order reliability methods (FORM), indicates that these two methods match very well.